Eksistensi Perkawinan Silariang dan Penyelesaiannya dalam Hukum Adat ditinjau dari Perspektif Hukum Islam - Azwar Azwar; Andi Sumardin; Ilyas Umar (Universitas Muslim Indonesia, 2021)
The case of silariang, or elopement, in South Sulawesi is mainly in Kel. South Empoang, Kec. Binamu, and Kab. Jeneponto. From then until now, it still happens often. Silariang performers don't seem to care about the sanctions or threats they will face, even though they know that what they are doing can face badik (stabbing). For those who do silat, as long as love is turbulent in their hearts, they will face death. The main problem in this research is to examine the problems or problems regarding crossbreeding that often occurs in Kel, South Empoang, Kec., Binamu Kab., and Jeneponto. The purpose of this research is to find out the factors that cause cross-breeding marriages and how the traditional forms of settlement of cross-breeding cases in Kel, South Empoang, Kec., Binamu Kab., Jeneponto. Based on information obtained from various sources, the people of Jeneponto have three habits in resolving crossbreeding cases: 1) killing Silariang perpetrators; 2) assuming that Silariang perpetrators have died; and 3) waiting for Silariang perpetrators to return home well and peacefully. The first and second habits above are contrary to Islamic law, while the third habit is in line with or in accordance with Islamic law